In vivo Mouse Intervertebral Disc Degeneration Models and Their Utility as Translational Models of Clinical Discogenic Back Pain: A Comparative Review - Tang, Shirley N.; Walter, Benjamin A.; Heimann, Mary K.; Gantt, Connor C.; Khan, Safdar N.; Kokiko-Cochran, Olga N.; Askwith, Candice C.; Purmessur, Devina (Frontiers in Pain Research, 2022)
Low back pain is a leading cause of disability worldwide and studies have demonstrated intervertebral disc (IVD) degeneration as a major risk factor. While many in vitro models have been developed and used to study IVD pathophysiology and therapeutic strategies, the etiology of IVD degeneration is a complex multifactorial process involving crosstalk of nearby tissues and systemic effects. Thus, the use of appropriate in vivo models is necessary to fully understand the associated molecular, structural, and functional changes and how they relate to pain. Mouse models have been widely adopted due to accessibility and ease of genetic manipulation compared to other animal models. Despite their small size, mice lumbar discs demonstrate significant similarities to the human IVD in terms of geometry, structure, and mechanical properties. While several different mouse models of IVD degeneration exist, greater standardization of the methods for inducing degeneration and the development of a consistent set of output measurements could allow mouse models to become a stronger tool for clinical translation. This article reviews current mouse models of IVD degeneration in the context of clinical translation and highlights a critical set of output measurements for studying disease pathology or screening regenerative therapies with an emphasis on pain phenotyping. First, we summarized and categorized these models into genetic, age-related, and mechanically induced. Then, the outcome parameters assessed in these models are compared including, molecular, cellular, functional/structural, and pain assessments for both evoked and spontaneous pain. These comparisons highlight a set of potential key parameters that can be used to validate the model and inform its utility to screen potential therapies for IVD degeneration and their translation to the human condition. As treatment of symptomatic pain is important, this review provides an emphasis on critical pain-like behavior assessments in mice and explores current behavioral assessments relevant to discogenic back pain. Overall, the specific research question was determined to be essential to identify the relevant model with histological staining, imaging, extracellular matrix composition, mechanics, and pain as critical parameters for assessing degeneration and regenerative strategies.